Analysis of the animated video "Healthy body, strong growth" in growing Post-COVID-19 Obesity Risk Awareness - Rosyad, Aulia Sabila (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aimed to analyze the making of the animated video "Healthy Body, Grow Strong" in building awareness of the risks of post-covid-19 obesity. The research method used was descriptive qualitative research method and looking for the necessary data by means of literature studies. The results of the research conducted obtained that the animated video PSA "Healthy Body, Grow Strong" itself was produced with the aim of building awareness about the risk of obesity after COVID-19 and urging to prevent it by living a healthy lifestyle